MEDIA LITERACY IN KINDERGARTEN - SIMBARTL, Petr (Trends in education, 2017)
This paper addresses the issue of media competence in kindergarten. We look at it as a coherent structure consisting of many components. We discuss the contents of the curriculum document " Rámcově vzdělávacího programu pro předškolní vzdělávání (RVP PV)" as it solves media competencies. We are looking for possible parts that help to promote this topic. The article is then supplemented mainly by the results of research focusing on the media literacy of the population under 15 in the Czech Republic and the results of empirical research in Germany "Die Förderungvon Medienkompetenz im Kindergarten". These were important findings. Based on these and other findings, new research goals arise for us.
Keywords: media competences; early childhood education; media education